OUTDOOR EDUCATION - Et, Sümeyra Zeynep (Emerald Publishing, 2024)
The educational paradigm of 21st century calls for taking uniqueness of individuals into account, developing unique potentials, and seeking for the necessary conditions to realize these individual abilities. Among the conditions of self-realization is outdoor education (Yıldız et al., 2022). The term ‘outdoor education’ as a broad term that refers to organized learning that takes place (Asfeldt et al., 2021). Outdoor education is often referred to as outdoor le outdoor schools, forest schools, and wilderness education and these are examples of experiential learning (Fang et al., 2023). There is a growing body of research investigating the outcomes and benefits of outdoor education. These outcomes and benefits include lifelong learning, environmental literacy and sustainable education goals, outdoor skill development, personal and social skill development (Asfeldt & Hvenegaard, 2014; Dyment & O’Connell, 2007; Hutson & Weber, 2008; Wigglesworth & Heintzman, 2017), building a sense of community (Asfeldt et al., 2017), outdoor expeditions as holistic integrated learning (Harper & Webster, 2017), and the value of combining outdoor skills training, place stories, outdoor journeys as a means of enhancing nature place relationships (Mikaels & Asfeldt, 2017) and increased their degree of nature connectedness (Braun & Dierkes, 2017). Thus, outdoor education has become associated with many different learning contents. Some of them are as follows; earth education, bio-regional education, expedition learning and expansion training, ecological education, natural awareness, natural experience, local-based teaching and education, and the use of environmental materials as learning to integrate the local environment (Fang et al., 2023). Despite all these benefits fear and concern about health and safety, teachers’ lack of confidence in teaching outdoors, school curriculum requirements, shortages of time, resources (Dillon et al., 2006) overshadow the gains achieved from outdoor education (Abbott & Flynn, 2022). In this context, it seems important how education and teachers offer learning opportunities to students in the open air (Borsos et al., 2022). All the above-mentioned elements of outdoor education. © 2024 by Information Age Publishing.
Keywords: Outdoor Education; Outdoor Experiential Learning; Outdoor Learning